Desafios aos direitos e garantias fundamentais: fraudes à Constituição - Lisbôa, Natália de Souza (2009)
This paper deals with frauds against the Constitution and the threat that its use entails fundamental rights and guarantees. In the first place, Constitution are carried out by the Legislative Branch, holder of the reforming power promulgate amendments to the Constitution that are born with the purpose of constitutionalizing a law that was originally unconstitutional, thus already proclaimed through diffuse control, preventing the protection of material right violated by such laws by the diffuse and concrete. As the constitutionally guaranteed rule is that of non-rotation, a constitutional amendment can not be issued to give effect to a law that initially lacked it, such legislative activity also affects the fundamental rights and guarantees constitutionally foreseen.